Proceedings of the 9th International Conference on Computer Supported Collaborative Learning - CSCL'09 2009
DOI: 10.3115/1600053.1600087
|View full text |Cite
|
Sign up to set email alerts
|

When is collaborating with friends a good idea? insights from design education

Abstract: Prior research is split on the relationship between prior friendship and performance. Based on our review of the literature, we highlight areas where further research is needed to achieve greater practical applicability of the results. We then present our study measures and preliminary analysis of data collected from a design studio university course. Our quantitative and qualitative probes suggest a link between teammates' prior friendship and lower performance outcomes. We also identify four group processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In contrast, Maldonado et al (2009) found a strong negative correlation between prior friendship and groupwork performance. Furthermore, working with friends can yield lower-quality outcomes because friends indulge in more non-task related behaviour, with stronger pressures to agree, and unwillingness to be critical of each others' ideas (Dutson et al, 1997;Witmer and Singer, 1999).…”
Section: Related Workmentioning
confidence: 48%
See 1 more Smart Citation
“…In contrast, Maldonado et al (2009) found a strong negative correlation between prior friendship and groupwork performance. Furthermore, working with friends can yield lower-quality outcomes because friends indulge in more non-task related behaviour, with stronger pressures to agree, and unwillingness to be critical of each others' ideas (Dutson et al, 1997;Witmer and Singer, 1999).…”
Section: Related Workmentioning
confidence: 48%
“…So while prior social relationships may not be necessary for collaboration (Maldonado et al, 2009;Witmer and Singer, 1999), some social familiarity does appear to promote group interaction and performance. When technology is being used to mediate learning prior to meeting face-to-face, it is advisable to help participants develop common groups so they can adapt their modus operandi to the technology.…”
Section: Discussionmentioning
confidence: 93%
“…Such knowledge may help develop strategies for team formation. A complication with this issue though is that friends do not always make the best project teammates, because they tend to avoid conflict and excuse lower effort [24]. For individual employees, social network information can assist employees in finding jobs [14] and in spreading information between organizational divisions [16].…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Some have argued the presence of friends can distract from learning and interfere with productivity (Zajac & Hartup, 1997). Working with a friend may relax partner expectations such that pressure to perform is reduced (Maldonado, Klemmer, & Pea, 2009). When friends are present, off-task behaviors can increase, which tends to limit on-task discussion (So & Brush, 2008).…”
mentioning
confidence: 99%
“…Together, these conspire to reduce effort invested in task completion. In one study of college undergraduates, ratings of friendship were negatively correlated with performance on a design project (Maldonado et al, 2009). Compared to nonfriends, friends proposed plans that were less well-developed and submitted final projects that were of poorer quality.…”
mentioning
confidence: 99%